Implementation of Risk Management Development Principles - Fitri yulia; Yenita Anggraini Barus; Yusuf Hadijaya; Muhammad Dalimunthe (Universitas Muhammadiyah Enrekang, 2025)
Risk management is the process of identifying, analyzing, and mitigating risks that may be faced by an organization or individual in achieving certain goals. Although risk management has many benefits, there are still various challenges in its implementation. Some of them are lack of understanding and awareness of the importance of risk management, limited resources, and resistance to change. Therefore, an appropriate strategy is needed so that the principles of risk management can be applied optimally. The purpose of this study is to discuss the application of risk management development principles in various sectors, the challenges faced, and recommendations to improve its effectiveness. It is hoped that this paper can provide deeper insight into the importance of risk management in supporting organizational sustainability. The research method that will be used in this study is a qualitative research method with a descriptive approach. The results of the study show that the application of effective risk management principles can help organizations anticipate and overcome various challenges and minimize possible negative impacts. In addition, risk management not only functions as a threat mitigation tool, but also as a means to increase organizational competitiveness. awareness and commitment from all elements in the organization are essential to ensure the success of risk management implementation.